USING VIDEO MATERIALS IN TEACHING LISTENING SKILLS FOR B1 LEARNERS - Jumaniyozova Moxinur,; Tulyaganova Nargiza, (Ustozlar uchun, 2025)
The purpose of this article is that to improve listening skills with video materials. The data collection was accomplished by means of students' reflection questionnaires posterior to the video sessions, field notes of the investigators, interviews and comprehension tests. The analysis was based on a constant comparison of data that were triangulated after being coded and categorized. The findings suggest improvement in the students´ listening skill, as well as, in the acquisition of vocabulary and in the practice of pronunciation. Pedagogical and research implications were included.